The modernity/coloniality of being: Hegemonic psychology as intercultural relations. (January 2018) - Adams, Glenn; Estrada-Villalta, Sara; Gómez Ordóñez, Luis H.
Abstract: Decolonial approaches consider modernity in terms of its inherent "dark side", coloniality : ways of thinking, feeling, and being associated with European global domination. We apply a decolonial approach to illuminate the coloniality inherent in the independent selfways that constitute standards of hegemonic psychological science. On one hand, these modern ways of being are the product of colonial violence that enabled their characteristic sense of abstraction from context. On the other hand, the promotion or growth orientation associated with these modern/colonial ways of being reproduces domination. We trace consequences of the modernity/coloniality of being for intercultural relations in a discussion of limited-good or closed-system mentalities that are prevalent in many communities of the Global South. Standard scientific accounts represent these mentalities as a form of pathology. A decolonial response emphasizes not only how these mentalities contribute to collective well-being, but also how independent selfways and associated delusions about unlimited good afford intercultural relations of (colonial) domination inherent in modernity.